(untitled) (Research, Society and Development, 2022)
Introduction: Acute myocardial infarction (AMI) is a serious disease with ischemic alteration, from a clot that prevents blood flow causing cell death of a fragment of heart muscle, which can cause physical, psychological and social sequelae. Objective: To characterize the epidemiological situation of acute myocardial infarction in the city of Maceió, Alagoas from 2010 to 2020, in order to analyze deaths, hospitalizations and their possible causes. Method: This is a descriptive observational epidemiological study, with a quantitative approach using secondary data from health information obtained from the Mortality Information System (SIM) and Hospital Information System (SIH) databases. Result/Discussion: The year 2019 had the highest coefficient of deaths from AMI and a decrease in the year following which the Covid-19 pandemic began in Brazil, which may be associated with a supposed inadequacy of notifications, when the overload of services was intensified, compromising the quality of information. Hospitalizations increased by 26 more cases in the same year. Conclusion: The study made it possible to know the epidemiological situation in the region, which is necessary for an efficient and quality management of this population.